The potential of public participation to facilitate infrastructure decision-making: Lessons from the German and European legal planning system for electricity grid expansion. (October 2016) - Schweizer, Pia-Johanna; Bovet, Jana
Abstract: The article examines the potential role that public engagement and participative pro-cesses to play a role in effective infrastructure planning in the context of energy policies. For example, by 2050, at least 80% of Germany's electricity has to be derived from re-newable energy sources if Germany is to meet the goals of its own energy policy. This includes the comprehensive and accelerated extension of the electricity grid. As a result of the magnitude of these changes, the German energy transition is not proceeding without debate and controversy. Public engagement is certainly no panacea for en-hanced social acceptance, yet it offers substantial potential to facilitate the energy tran-sition. The paper draws together social science and legal expertise in order to investi-gate the role of public participation in legal planning processes concerning energy infra-structures. The paper not only focuses on the extension of the German power grid, but also deals with participative policy at the European level. To this end, the paper analyzes the potential role of the German legal planning system in grid expansion and in the Eu-ropean processes of nominating Projects of Common Interest (PCI) and of drawing up the Ten Year Network Development Plan (TYNDP).